Study of thermal diffusivity of Zn/Al layered double hydroxide synthesized with different molar ratio of Zn/Al salts - Ranjbar, Maryam; Shameli, Kamyar; Ahmad @ Ayob, Mansor; Mat Yunus, Wan Mahmood; Hussein, Mohd Zobir; Shameli, Kaveh (Institute of Materials Physics, 2014)
Thermal diffusivity of zinc-aluminum layered double hydroxides synthesized at different molar ratios of Zn to Al; at pH 7, 8 and 10 were measured using polyvinlidene diflouride (PVDF) photoflash technique. The samples were prepared using Zn (NO3)2 and Al (NO3)3 solutions by dropwise addition of NaOH solution with vigorous stirring under nitrogen atmosphere. The different ratios of Zn to Al were obtained by changing the molar ratio of Zn (NO3)2 to Al (NO3)3 solutions. The slurry formed was kept at 70 °C in an oil bath shaker for 18 h and then filtered, washed and dried in an oven for another 48 h at 70 °C. A simple photoflash and PVDF transducer were used as light source and thermal wave detector, respectively. All the measurements of thermal diffusivity of Zn-Al layered double hydroxide were carried out at room temperature. Thermal diffusivity for all series of sample prepared at pH=7, 8 and 10 increase from R=3 to R=5. Thermal diffusivity values of zinc-aluminum layered doubled hydroxide synthesized at pH 8 are higher than the values obtained for samples prepared at pH=7 (except for R=5) and at pH 10 are highest than two other series at pH 7 and 8.